Methods of quantitative determination of Sparteine hydroiodine - M. E. Blazheyevskyy; М. М. Kucher; V. V. Dyadchenko; I. O. Yurchenko (Zaporozhye State Medical University, 2015)
Currently, there are many different methods of quantitative determination of alkaloid Sparteine amounts such as gravimetry, acidimetry, argentometry (including the use of ion-selective electrode), iodometry, extraction photometry, colorimetry, amperometry, potentiometry, direct ionometry with ion-selective electrode, thin layer chromatography, high-performance liquid chromatography and high pressure gas chromatography, also infrared and Nuclear magnetic resonance spectroscopy, chromatography-mass-spectrometry. It has been analyzed that most of the well-known methods are too insensitive, indiscriminate or too expensive, time-consuming and inaccessible. An application for analysis of amperometric titration techniques using both analytical reagent heteropolianions (GPA) Kehhina structure - standard solution 12-molibdophosphoric heteropolyacid and method of direct potentiometric determination using ISE for determining the choice amounts or amounts of alkaloids qinolizidine series in extracts are very promising, relatively simple in execution, express and sufficiently sensitive.